(3TQM GdeaVdjGJs - (3CHi Ydj CMeO Hf eMeO Hf GdMSf GdeQRhbis; (3GdeanqVd Hf eMeO Hf jYdi Hf YGeQ GdVHj, CHh GdYHGS,J (B168 (3g` ? s
(3ChdgG (B:s
(3GdMeO ddg GdYdi GdTCf GdLd GdHQgGf GdHGOF Ndbg HfYeI bHd s
(3BNQgG (B:s
(3hhGMOgG TGFd heYfi QGMJ QLYJ ef GdeQYi Gi VQHfG HGdbOGM dJfMQ dg s
(3GdeaVdjGJ gi GNJjGQ GdeaVd GdVHi GdeJhai (B168(3g` ef GdTYQs
(3GfXQ ai GdLRA GdChd GdCQbGe (B557 -559 (3COH HTQMi GHf GdCfHGQi hGdNWjH GdJHQjRis
(3ChdgG JQLeI eNJUQI ddeQRhbi hJedcGf eDQNGf(B1027 (3g` h (B1195(3g`s
(3agQS HbUGFO GdeaVdjGJ GdeTQhMI s
(3HBNQ UaMGJgG JYbjHI s
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs